Massless spectra of three generation U(N) heterotic string vacua - Blumenhagen, Ralph; Weigand, Timo (Arxiv, 2006)
We provide the methods to compute the complete massless spectra of a class of recently introduced supersymmetric E8 x E8 heterotic string models which invoke vector bundles with U(N) structure group on simply connected Calabi-Yau manifolds and which yield flipped SU(5) and MSSM string vacua of potential phenomenological interest. We apply Leray spectral sequences in order to derive the localisation of the cohomology groups H^i(X,V_a × V_b), H^i(X,\bigwedge^2 V) and H^i(X,{\bf S}^2 V) for vector bundles defined via Fourier-Mukai transforms on elliptically fibered Calabi-Yau manifolds. By the method of bundle extensions we define a stable U(4) vector bundle leading to the first flipped SU(5) model with just three generations, i.e. without any vector-like matter. Along the way, we propose the notion of Lambda-stability for heterotic bundles.